2008
DOI: 10.1002/qua.21648
|View full text |Cite
|
Sign up to set email alerts
|

Computations on three isomers of La@C74

Abstract: Density-functional theory calculations are presented for La@C 74 , where C 74 is either the IPR (isolated pentagon rule) cage or two cages with a pentagon-pentagon junction. Their relative thermodynamic production yields are evaluated using the calculated terms, and it is shown that the IPR-based endohedral prevails at relevant temperatures in agreement with the observation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The role of the sole IPR cage is however quite different in the La@C 74 isomeric system. The La@C 74 isomer with the IPR cage ( Figure 3 ) is the lowest in energy [ 25 ] and the non-IPR species are located rather high. Temperature developments of the relative concentrations of the three La@C 74 isomers in the RRHO and FEM treatments are presented in Figure 4 —it is a system where the populations from the two approaches are considerably different.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of the sole IPR cage is however quite different in the La@C 74 isomeric system. The La@C 74 isomer with the IPR cage ( Figure 3 ) is the lowest in energy [ 25 ] and the non-IPR species are located rather high. Temperature developments of the relative concentrations of the three La@C 74 isomers in the RRHO and FEM treatments are presented in Figure 4 —it is a system where the populations from the two approaches are considerably different.…”
Section: Resultsmentioning
confidence: 99%
“…The metallofullerenes based on the C n ( n = 72, 74, 76) cages have also been computed [ 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. The first relative isomeric stabilities were evaluated [ 21 , 22 ] for Ca@C 72 and Ca@C 74 and it was shown that the non-IPR encapsulations are significant only in Ca@C 72 .…”
Section: Introductionmentioning
confidence: 99%
“…Haufe et al [18] have also prepared the new alkaline earth metal endohedral fullerenes M@C n (M = Ca, Sr, Ba; n = 74, 76) by means of the RF-method, and proved that the spectroscopic data are successful isolation of the two IPR-isomers Sr@C 76 -I and II. Additionally, the geometries and electronic properties of M@C 74 (M = Be, Mg, Ca, Sr, and Ba) [21][22][23][24], M@C 60 (M = Li, Na, and Cs) [25,26], La@C 72 [27], M@C 74 (M = Sc, La) [28][29][30], Yb@C 74 [31], and La@C 82 [32,33] have been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[4–8] A great number of applications ascribe mainly to their unique physical and chemical properties such as electrical conductance, ferroelectricity, nonlinear optical properties, and so forth. Especially, the hollow fullerene cages can be modified with the targeted structures and interesting electronic features by means of the endohedral atoms[9–17] and small molecules[18–22] or exohedral species,[23–25] and then establish the novel form of carbon materials, and extend the scope of applications. For understanding their potential applications, the structural and electronic properties of each fullerene derivative are an essential prerequisite and should be first explored.…”
Section: Introductionmentioning
confidence: 99%